Identifikasi Senyawa Flavonoid dalam Fraksi n-Butanol Taraxacum officinale, Asteraceae - Wiwi Winarti; Ratna Djamil; Indah Yuniasari (Fakultas Farmasi Universitas Pancasila, 2007)
Herbs of Taraxacum officinale, a native of Europe, contain a flavonoid, steroid/triterpenoid, saponin, tanin, and a volatile oil. The purpose of this research was to determine the flavonoid substances, after partitioning of the methanolic extract by the Charaux-Paris method with n-butanol. Identification by uv-visible spectrophotometry confirmed that flavonoid from isolate la was a flavonol with an OH at 3, 7 position, oxygen at 6 or 8, while isolate III, also a flavonol, showed an OH at 3, 7 position, oxygen at 6 or 8, and besides that an additional o-diOH attached to ring B.